Aesthetic preference in the production of image sequences - Monroy, Ernesto; Orgs, Guido; Sagiv, Noam (Frontiers in Psychology, 2023)
This research uses the production method to study aesthetic preference for sequences of human body postures. In two experiments, participants produced image sequences based on their aesthetic preferences, while we measured the visual aesthetic features displayed in the compositions. In Experiment 1, participants created static images sequences based on their preference. Smooth continuation of significant objects was the preferred order. In Experiment 2, participants sorted images into apparent motion sequences they preferred to view. Participants preferred abstract images with local sequential symmetry and human body postures exhibiting global sequential symmetry. Our findings are compared to those of previous studies that employed the more widely used method of choice. Our experiments propose novel methods and conceptualisations for investigating aesthetic preferences for human body movement and other types of stimulus sequences.